Relatório final de estágio da prática de ensino supervisionada: aprender a ler e a escrever com respeito por si próprio e pelos outros - Santos, Fátima (2015)
This report is the result of the teaching practice held under the module of Supervised Teaching I, II and III, the Masters in Early Childhood Education and Teaching 1st Cycle of Basic Education. The purpose of it is to expose the work, documenting some of the experiences along the intership Kindergarten and 1st Cycle of Basic Education, at College Valsassina in Lisbon. This document is organized into two chapters: the first is reports the intership in for pre-school stage and the second stage in the 1st Cycle of Basic Education. In each institution and is characterized group of children is presented pedagogical work in the classroom and the most significant works. In both contacts had autonomy in the proposed activities. I tried to encourage and sensitize children to the presence of values in everyday life. To develop the activities the group diagnosed, I prepared work proposals, strategies and resources and reflected on the procedures followed and results obtained. The chapters differ in that in the contexto of Preschool education there is a subchapter concerning a Problem that there occurred, "group management", and is the 1st Cycle of Basic Education there is a subchapter concerning Project entitled "Learning to read and write with respect". Because I already knew the group, from Kindergarten, 1st Cycle of Basic Education activities were more easily adapted to the needs of the children. This report also aims to reflect on the paths followed in the interships.